2019
DOI: 10.3389/fmicb.2019.01003
|View full text |Cite
|
Sign up to set email alerts
|

Guarani Virophage, a New Sputnik-Like Isolate From a Brazilian Lake

Abstract: Virophages are critical regulators of viral population dynamics and potential actors in the stability of the microbial networks. These small biological entities predate the replicative cycle of giant viruses, such as the members of the Mimiviridae family or their distant relatives, which produce within the cytoplasm of their host cells a viral factory harboring a complex biochemistry propitious to the growth of the smaller parasites. In this paper, we describe the isolation and the chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
62
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(66 citation statements)
references
References 52 publications
(87 reference statements)
3
62
0
Order By: Relevance
“…Figure 5a shows that mutant Guarani decreases the replication of Tupanvirus DNA by approximately 3-fold. This low inhibition rate appears relatively similar to what has been found between the wild-type strain and APMV 24 . Experimental studies supported by bioinformatic analyses have shown that in contrast to their virus hosts, virophages become active during a late phase of giant virus infection 17,24,35 .…”
Section: Virophage Infection Leads To Tupanvirus Eliminationsupporting
confidence: 87%
See 4 more Smart Citations
“…Figure 5a shows that mutant Guarani decreases the replication of Tupanvirus DNA by approximately 3-fold. This low inhibition rate appears relatively similar to what has been found between the wild-type strain and APMV 24 . Experimental studies supported by bioinformatic analyses have shown that in contrast to their virus hosts, virophages become active during a late phase of giant virus infection 17,24,35 .…”
Section: Virophage Infection Leads To Tupanvirus Eliminationsupporting
confidence: 87%
“…The Guarani genome consists of a circular dsDNA genome of 18,967 base pairs encoding 22 predicted genes very similar to Sputnik 24 . We found that the virophage isolated from APMV supernatant has no mutations in its genome compared to the original strain that we sequenced previously 24 . We therefore consider this strain to be the wild-type genotype of the virophage.…”
Section: Potential Host Range Mutation Associated With the Host Acquimentioning
confidence: 68%
See 3 more Smart Citations